Thugs and village politics: Analysis of social capital in the dynamics of village head elections in Sinjai Regency - Agustirawati, Agustirawati; Sukri, Sukri (Institute Of computer Science (IOCS), 2025)
The election of village heads is one form of democracy in the village. The concept of democracy is what provides the basis and mechanism of power based on the principle of equality and human equality. Democracy places humans as the owners of sovereignty which is then known as the principle of people's sovereignty. To fulfill the rights of each human being cannot be achieved by each person individually, but must be together. Along with the rapid development and construction as an impact of globalization, the phenomenon of thuggery has emerged as one of the negative impacts that occur indirectly from the development of globalization. The phenomenon of the emergence of political thuggery must be prevented as early as possible by all existing political forces, and political parties are actually most responsible for the emergence of this political thuggery, especially for political parties, either directly or indirectly, which encourage the emergence of mass action and the plundering of government power.